Biodiversity increases and decreases ecosystem stability. (1st November 2018) - Pennekamp, Frank; Pontarp, Mikael; Tabi, Andrea; Altermatt, Florian; Alther, Roman; Choffat, Yves; Fronhofer, Emanuel; Ganesanandamoorthy, Pravin; Garnier, Aurélie; Griffiths, Jason; Greene, Suzanne; Horgan, Katherine; et al.
Abstract Losses and gains in species diversity affect ecological stability1–7 and the sustainability of ecosystem functions and services8–13 . Experiments and models have revealed positive, negative and no effects of diversity on individual components of stability, such as temporal variability, resistance and resilience2, 3, 6, 11, 12, 14 . How these stability components covary remains poorly understood15 . Similarly, the effects of diversity on overall ecosystem stability16, which is conceptually akin to ecosystem multifunctionality17, 18, remain unknown. Here we studied communities of aquatic ciliates to understand how temporal variability, resistance and overall ecosystem stability responded to diversity (that is, species richness) in a large experiment involving 690 micro-ecosystems sampled 19 times over 40 days, resulting in 12, 939 samplings. Species richness increased temporal stability but decreased resistance to warming. Thus, two stability components covaried negatively along the diversity gradient. Previous biodiversity manipulation studies rarely reported such negative covariation despite general predictions of the negative effects of diversity on individual stability components3 . Integrating our findings with the ecosystem multifunctionality concept revealed hump- and U-shaped effects of diversity on overall ecosystem stability. That is, biodiversity can increase overall ecosystem stability when biodiversity is low, and decrease it when biodiversity is high, or the opposite with a U-shaped relationship. The effects of diversity on ecosystem multifunctionality would also be hump- or U-shaped if diversity had positive effects on some functions and negative effects on others. Linking the ecosystem multifunctionality concept and ecosystem stability can transform the perceived effects of diversity on ecological stability and may help to translate this science into policy-relevant information. Species richness was found to increase temporal stability but decrease resistance to warming in an experiment involving 690 micro-ecosystems consisting of 1 to 6 species of bacterivorous ciliates that were sampled over 40 days.